EFFECTIVENESS OF MAGNETOTHERAPY IN THE TREATMENT OF PATIENTS WITH LUMBAR SYNDROME (Zdravstveni glasnik, 2024)
Introduction: The term low back pain means a feeling of pain at rest or during movement in the lower,lumbar part of the spine. In order to reduce pain, various physical procedures are used: electrotherapy,thermotherapy, laser therapy, magnetotherapy, ultrasound therapy, cryotherapy, kinesitherapy and manualmassage. Aim: To examine the effectiveness of magnetotherapy in the treatment of patients with lumbarsyndrome. Materials and Methods: The study included patients treated from 01.01.2013. to 31.12.2015. yeardue to the diagnosis of lumbar pain syndrome in persons whose treatment process included magnetotherapyin the "Beljan" practice as a research group where were treated 113 patients (73 male and 40 female). Therewere 262 (114 male and 148 female) patients in the Health Center in Metković as a control group in whichmagnetotherapy was not included in the treatment of any patient. Pain was assessed on the basis of a visualanalogue scale. Results: Research showed that the Chi-square test showed a statistically significantdifference between the duration of physical therapy by days between the examined and control groups,χ2(2,n=375) = 237.715; p